INTRODUCTION TO BUSINESS CORRESPONDENCE IN IN-HOUSE TRAINING AT SMK NU GEBANG - Pratika Ayuningtyas; Caecilia Rosma Widiyohening; Lutfi Ashar Mauludin (Jurnal Layanan Masyarakat, 2022)
The high unemployment rate in Indonesia, with most of them are the Vocational High School’s graduates. It triggers the vocational schools to improve the competence of their graduates that they will be part of the industry and business. One of the steps taken by the school based on the applicable laws and regulations is On-the-job training (Prakerin). However, the Covid-19 pandemic that hit Indonesia made it impossible to carry out as usual. SMK NU Gebang took steps to fill this void by holding In-House Training as a substitute for internships. One of the materials provided in the In-House Training is Business Writing on the topic of Introduction to Business Correspondence. This activity was attended by 16 students of class XI of the Financial Accounting study program and the NU Gebang Vocational School. This activity is carried out for approximately one month (May – June 2022). The method used in this activity is the lecture of material with direct practice. From this activity, it is known that SMK NU Gebang students are actively involved in participating in the In-House Training. Students can also complete the assigned tasks well.